The ‘Other’ as the subject’s constitutive element in various narratives: S. B. feat. S. B. - Bogutovac, Dubravka (2010)
The short story „Svetislav Basara intervjuiše Semjuela Beketa za Treći program Radio-Beograda“ („Svetislav Basara Interviews Samuel Beckett on the Third Channel of the Radio Belgrade“ by David Albahari is the starting point of the analysis that questions the poetical connections of the Basara and Beckett's fiction. In so doing, the central interests are Beckett's novel „Molloy“ and Basara's fictions „Priče u nestajanju“ („Vanishing Stories“), „Kinesko pismo“ („Chinese Letter“) and „Peking by Night“. The article discusses the status of the selected concepts from Albahari’s short story (“shapelessness”, “speech”, “frame”, “rain”, “pause”, “monologue”, “dialog”, “silence”, “darkness”, “unvisited place”, “work” and “emptiness”) in the context of poetics by the given authors. The reference model for the analysis is the M. Solar’s thesis on the three relatively separated basic methods/modalities of discussing postmodernism: applying the key procedures of the event history to one particular artistic domain (Jencks), defining the key attributes of an epoch (Lyotard) and the determination of the key characteristics of the arbitrarily selected texts (Lodge). In so doing, we are especially interested in the last approach, because ˗ unlike the first two ˗ it limits analysis to the level of discourse on literature and sets out literary procedures that characterize postmodern fiction (such as: antithesis, permutation, discontinued sequence, coincidence, extravagance and short circuit). On the abstract level, Basara’s „Priče u nestajanju“, „Kinesko pismo“ and „Peking by night“, just as Beckett’s „Molloy“, mediate existential convulsion of the subject faced with the emptiness and nothingness whereat the writing turns out to be the compulsion, but also the prolongation of death. Therefore, Basara’s fiction represents the rich potential for intertextual openness, which will be confirmed in the article with the additional comparative analysis on the concept of characters/storytellers.